60 GHz Indoor Propagation Studies for Wireless Communications Based on a Ray-Tracing Method. (8th January 2007) - Lim Lim, C.-P. C.-P.; Lee Lee, M. M.; Burkholder Burkholder, R. J. R. J.; Volakis Volakis, J. L. J. L.; Marhefka Marhefka, R. J. R. J.
Abstract : This paper demonstrates a ray-tracing method for modeling indoor propagation channels at 60 GHz. A validation of the ray-tracing model with our in-house measurement is also presented. Based on the validated model, the multipath channel parameter such as root mean square (RMS) delay spread and the fading statistics at millimeter wave frequencies are easily extracted. As such, the proposed ray-tracing method can provide vital information pertaining to the fading condition in a site-specific indoor environment.